Uroplastin, Its Nature and Its Excretion Pattern in Health and in Certain Disease States - Joist, H; Alkjaersig, Norma (Thrombosis and Haemostasis, 1967)
Experimental studies with a partially purified, potent procoagulant from human urine are reported. The material having the electrophoretic property of a â-globulin appears to functionally closely resemble tissue thromboplastin. A significant difference in the excretion of this pro coagulant between normal males and females and deviations from the normal excretion pattern in patients with impaired kidney function and certain other disease states are demonstrated. Possible pathophysiological implications of these findings are discussed.